External handheld loads affect scapular elevation and upward rotation during shoulder elevation tasks - Alan Eldridge; Everett Lohman; Skulpan Asavasopon; Lida Gharibvand; Lori Michener (International Biomechanics)
Altered scapular kinematics is associated with shoulder pain. Resistance exercise is a common treatment; however, the effects of lifting an external load on scapular kinematics is limited. Understanding whether an external handheld load affects scapular kinematics in a healthy population can provide normal values utilized for comparison to individuals with shoulder pain. Currently, no studies have examined the effect of incrementally increased handheld loads. We defined the effects of varying external handheld loads on scapular kinematics during a shoulder elevation task. Healthy participants (n = 50) elevated their shoulder in the scapular plane over 4 trials. One trial of no loading (control) and 3 trials with incrementally increased external handheld loads. Scapular kinematic rotations and translations were measured during ascent and descent phases using 3D motion capture. Compared to no load, the highest external load during ascent increased scapular elevation [mean difference = 3.2 degrees (95%CI: 0.9, 5.4), p = 0.006], and during descent increased scapular elevation [mean difference = 3.9 degrees (95%CI: 2.8, 5.1), p < 0.001] and increased scapular upward rotation [mean difference = 4.5 degrees (95%CI: 2.4, 6.6), p < 0.001]. External handheld loads result in small increases in scapular elevation and scapular upward rotation. These results should be utilized as normal values to compare to individuals with shoulder pain.